2018
DOI: 10.1098/rstb.2017.0223
|View full text |Cite
|
Sign up to set email alerts
|

New substrates for stem cell control

Abstract: The capacity to culture stem cells in a controllable, robust and scalable manner is necessary in order to develop successful strategies for the generation of cellular and tissue platforms for drug screening, toxicity testing, tissue engineering and regenerative medicine. Creating substrates that support the expansion, maintenance or directional differentiation of stem cells would greatly aid these efforts. Optimally, the substrates used should be chemically defined and synthetically scalable, allowing growth u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 85 publications
0
14
0
Order By: Relevance
“…Our work and that of others has shown that h-iPSC derived MNs usually coalesce into large cell clusters which gradually detach from the culture device (Kuijlaars et al 2016; Taga et al 2019; Thiry et al 2020). This situation is most likely due to the degradation of the protein-based substrate (Matrigel or laminin) commonly used for coating, a process that can mediated by enzymes secreted by the cells (reviewed in Schmidt et al 2018; Clement et al submitted). To address this shortcoming, we sought to test the effect of a non-peptide polymer substrate, dPGA, that was shown to improve primary neuron culture conditions, possibly due to its resistance to degradation by cell-secreted proteases (Clement et al submitted).…”
Section: Resultsmentioning
confidence: 99%
“…Our work and that of others has shown that h-iPSC derived MNs usually coalesce into large cell clusters which gradually detach from the culture device (Kuijlaars et al 2016; Taga et al 2019; Thiry et al 2020). This situation is most likely due to the degradation of the protein-based substrate (Matrigel or laminin) commonly used for coating, a process that can mediated by enzymes secreted by the cells (reviewed in Schmidt et al 2018; Clement et al submitted). To address this shortcoming, we sought to test the effect of a non-peptide polymer substrate, dPGA, that was shown to improve primary neuron culture conditions, possibly due to its resistance to degradation by cell-secreted proteases (Clement et al submitted).…”
Section: Resultsmentioning
confidence: 99%
“…Researches have shown that stem cells' shape and synthetic extracellular matrices can control their fate [12][13][14][15][16][17] . Also, the researches con rm the importance of surface topography for stem cell differentiation [18][19][20][21][22][23] .…”
Section: Introductionmentioning
confidence: 91%
“…The role of culture substrate in cellular behavior has been evaluated in several studies [9][10][11][12] . Also, researchers have confirmed the importance of surface topography for stem cell differentiation [13][14][15][16][17][18] .…”
mentioning
confidence: 88%